Interleukin-6-dependent growth in a newly established plasmablastic lymphoma cell line and its therapeutic targets - Mine, Sohtaro; Hishima, Tsunekazu; Suganuma, Akihiko; Fukumoto, Hitomi; Sato, Yuko; Kataoka, Michiyo; Sekizuka, Tsuyoshi; Kuroda, Makoto; Suzuki, Tadaki; Hasegawa, Hideki; Fukayama, Masashi; Katano, Harutaka (Scientific reports, 2017)
Plasmablastic lymphoma (PBL) is a rare, highly aggressive subtype of non-Hodgkin lymphoma with plasma-cell differentiation occurring typically in immune-suppressed patients such as those with AIDS. This study reports the establishment and characterization of a new cell line, PBL-1, derived from a patient with AIDS-associated PBL. Morphological assessment of PBL-1 indicated plasma-cell differentiation with a CD20(−) CD38(+) CD138(+) immunophenotype and IgH/c-myc translocation. The cell line harbours Epstein-Barr virus, but a 52.7-kbp length defect was identified in its genome, resulting in no expression of viral microRNAs encoded in the BamHI-A Rightward Transcript region. Importantly, supplementation of culture medium with >5 ng/mL of interleukin-6 (IL-6) was required for PBL-1 growth. Starvation of IL-6 or addition of tocilizumab, an inhibitory antibody for the IL-6 receptor, induced apoptosis of PBL-1. Transduction of IL-6 into PBL-1 by lentivirus vector induced autologous growth without IL-6 supplementation of culture medium. These data indicate the IL-6 dependency of PBL-1 for proliferation and survival. mTOR inhibitors induced cell death effectively, suggesting mTOR in the IL-6 signalling pathway is a potential therapeutic target for PBL. This established PBL cell line will be a useful tool to further understand the pathophysiology of PBL and aid the future development of PBL treatment.